Muslim Legal Pluralism in the West - Yilmaz, Ihsan. author. (orcid)0000-0001-8409-3045 Link aut Link
VII, 202 p. 1 illus.
Keywords: This book is a comprehensive introductory text to the subject of Western Muslims’ diverse interpretations, discussions and practices of Shari’a with a particular focus on their daily lives in the West. Through a series of interconnected chapters, the book navigates key themes such as Shari’a and legal pluralism, Shari’a vis-à-vis the experiences and political participation of Muslims in Western democracies, the role of religious scholars, the dynamics of Shari’a courts, Shari’a and multiple belongings, and transnational loyalties. Functioning as a comprehensive reader and handbook, the book offers non-experts a comprehensive understanding of the meaning and relevance of Shari’a in Western contexts, exploring how Muslims interpret and apply its principles in their lived experiences and challenging the one-dimensional narratives. Ihsan Yilmaz is a chair in Islamic Studies and research professor of political science and international relations at Deakin University’s ADI (Alfred Deakin Institute for Citizenship and Globalisation). Previously, he worked at the Universities of Oxford and London, demonstrating a strong track record of successfully leading multi-site international research projects. At Deakin, his projects have received funding from the Australian Research Council (ARC), Department of Veteran Affairs, Victorian Government, and Gerda Henkel Foundation. Denitsa P. Sokolova-Shipoli has a Ph.D. in Political Science and International Relations and is currently a Visiting Scholar in the Edmund A. Walsh School of Foreign Service, Georgetown University. Her academic focus is on foreign policy, democracy, religion, human rights, and minorities.